Re-branding Colombia through Urban Transformation and Rural Regional Marketing - Muñiz Martínez, Norberto (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
Colombia is now projecting a new, positive image to the world after overcoming a past characterised by politically inspired guerrilla warfare and violent conflict with narco-trafficking cartels which had ravaged the country for decades. Even before the country’s transformation, other intermediate place institutions – cities and regions – had already taken significant steps towards territorial change and marketing. This paper outlines the processes involved in urban and social transformation in the city of Medellín and in the marketing of the coffee region, as illustrative cases of city re-branding and regional branding, respectively.